Recognition of the contract not concluded as the way of protecting civil rights and interests by the court (Bulletin of Kharkiv National University of Internal Affairs, 2018)
The article is focused on clarifying the possibility of using this method of protection of civil rights and interests as recognition of the agreement not concluded. On the basis of the analysis of legal doctrine and judicial practice the author has concluded about the feasibility of recognizing this method. The author of the paper has stressed that not concluded agreement according to its legal nature is not a legal fact, and therefore can not be the basis of any civil legal relationship including the contractual one. There is no corresponding legal fact (contract-transaction) – so, there are no consequences of this fact (contract-legal relations).It has been noted that the purpose of applying this method of protection, like the recognition of the contract not concluded, is the elimination of the legal uncertainty regarding the rights and obligations of the parties under the contract. Establishment of the fact of not concluded agreement is important above all to address the issue of applying the norms on contractual liability of the parties under the contract. In particular, in case of filing claims to the court for a penalty due to breach of a contract, the court must first of all establish the grounds for the recognition of the contract not concluded that, in turn, would impose the refusal to pay the penalty. Protection of the disputed right is realized by the court, not by traditional methods (restitution, compensation), but by ascertaining certain facts, including the recognition of the agreement not concluded.The claim for the recognition of a contract not concluded is not heard by the court according the rules of claim proceedings and can not be considered in the procedure of separate proceedings for establishing the fact that has legal value.It has been emphasized that “not concluded agreement” and “invalid contract” are not identical legal categories. This is primarily due to various legal grounds and consequences of using each of these methods of protection of civil rights and interests by the court. Recognition of the contract not concluded – is a special consequence of violating the law norms, which excludes the application of the invalidity of the transaction. In case of not concluded contract we apply the affects provided by the norms regulating the obligations of unjust enrichment, in case of invalid – the consequences prescribed by the law for invalid transactions. If in regard to not concluded contract the party has prematurely transferred the property, there are legal relations between the parties as a result of the acquisition, maintenance of the property without sufficient legal grounds – relations that belong to non-contractual.
Keywords: contract; legal fact; conclusion of the contract; not concluded contract; invalid agreement; invalid transaction